1999
DOI: 10.1006/viro.1999.9783
|View full text |Cite
|
Sign up to set email alerts
|

Defective nef Alleles in a Cohort of Hemophiliacs with Progressing and Nonprogressing HIV-1 Infection

Abstract: Deletion of the nef gene results in viral attenuation and confers protection against challenge with wild-type simian immunodeficiency virus in macaques. Regarding HIV-1 infection, a few long-term nonprogressors (LTNP) with nef deletions have been described. In this study, the nef genes of a group of seven LTNP and eight progressors, all belonging to the same cohort of infected hemophiliacs, were analyzed by cloning and sequencing from both virion RNA and peripheral blood mononuclear cell-associated proviral DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 54 publications
6
55
0
Order By: Relevance
“…Other studies have reported that LTNPs infected with HIV-1 from blood transfusions had very similar deletions in nef proviral DNA as members of the Sydney Blood Bank cohort (Brambilla et al, 1999;Deacon et al, 1995), which were statistically significant when compared with mutations found in progressors (Casartelli et al, 2003;Geffin et al, 2000). These attenuating deletions in nef have been shown to A TAC point mutation at position 138 (T138Q) in nef has been reported to occur more frequently in LTNPs versus progressors and is cited as being a cause of decreased viral fitness and replication (Kirchhoff et al, 1999;Premkumar et al, 1996;Tolstrup et al, 2006).…”
Section: Genomic Sequence Analysis Of Virus Genes From Controllersmentioning
confidence: 87%
“…Other studies have reported that LTNPs infected with HIV-1 from blood transfusions had very similar deletions in nef proviral DNA as members of the Sydney Blood Bank cohort (Brambilla et al, 1999;Deacon et al, 1995), which were statistically significant when compared with mutations found in progressors (Casartelli et al, 2003;Geffin et al, 2000). These attenuating deletions in nef have been shown to A TAC point mutation at position 138 (T138Q) in nef has been reported to occur more frequently in LTNPs versus progressors and is cited as being a cause of decreased viral fitness and replication (Kirchhoff et al, 1999;Premkumar et al, 1996;Tolstrup et al, 2006).…”
Section: Genomic Sequence Analysis Of Virus Genes From Controllersmentioning
confidence: 87%
“…However, because it is likely that the cellular responses induced by the two Tat vaccine modalities were distinct, further experimentation is required to resolve the relative contribution of humoral and cell-mediated immune responses to the anti-Tat protective immunity. It is important to note that other immune-evasion tactics used by HIV-1 also contribute to the establishment of chronicity and disease progression, and that this tactical redundancy allows for the loss of one activity, as in ⌬nef quasi-species (54 -56), without sacrificing the survival of the resultant virus and in some individuals without complete loss of virulence (56). The impact of immunity to Tat, therefore, will depend on these other parameters, and it is not surprising that the efficacy of Tat vaccines in animal models is inf luenced by the potency of the lentivirus challenge stock (31,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although the use of both SIV-infected Macaca and transgenic mouse systems generated consistent conclusions on the critical role of Nef in AIDS pathogenesis, 1,2 much more controversial data regarding the role that HIV-1 Nef expression plays in humans have been published. [66][67][68][69][70] We have already described how the internalization of extracellular Nef in MDMs could induce a preferential replication of T tropic, which is the HIV quasi species more represented in the later stages of the disease, 22 compared to M-tropic HIV variants. 23 Data presented here describe an additional consequence of Nef expression, that is, the alteration of the pattern of soluble factors released by monocytes/macrophages, which, in turn, could lead to modifications in the cross-talk between monocytes/macrophages and cells of the immune system.…”
Section: Hiv-1 Nef Induces Stat1 Activation In Macrophages 2759mentioning
confidence: 99%